A Global Projection Model for Euro Area Large Economies - Jakab, Zoltan (IMF Working Papers; Working Paper ;, 2015)
The GPM project is designed to improve the toolkit for studying both own-country and cross-country linkages. This paper creates a special version of GPM that includes the four largest Euro Area (EA) countries. The EA countries are more vulnerable to domestic and external demand shocks because adjustments in the real exchange rate between EA countries occur more gradually through inflation differentials. Spillovers from tight credit conditions in each EA country are limited by direct trade channels and small confidence spillovers, but we also consider scenarios where banks in all EU countries tighten credit conditions simultaneously.